Sustainable ground improvement method using encapsulated polypropylene (PP) column reinforcement - Muzamir, Hasan; M. S. I., Zaini; N. A. W., Hong; Abdul, Wahab; K. A., Masri; Putra Jaya, Ramadhansyah; Hyodo, M.; Winter, M. J.; Sholichin, M.; Haribowo, R. (IOP Science, 2021)
This study investigates the effectiveness of encapsulated polypropylene (PP) column in enhancing the undrained shear strength of kaolin (soft clay). The usage of PP in treating problematic soil is a more sustainable and cost-effective alternative compared to other materials. The installation of granular column can be done by using vibro-replacement method. Several geotechnical tests to determine the properties of materials were conducted. The shear strength of treated kaolin sample was examined by using Unconfined Compression Test (UCT). There are seven (7) batches of soil sample in total which included a control sample, three (3) batches of 14 mm and three (3) batches of 20 mm diameter PP column. Different diameters of PP column were examined with 60 mm, 80 mm and 100 mm height, respectively with soil sample of 50 mm in diameter and 100 mm in height. The shear strength improvement of kaolin is 33.82%, 46.51%, and 49.88% when implanted with a PP column with a 7.84 area replacement ratio and 0.6, 0.8 and 1.0 penetration ratio. The soft soil treated using 16.00 area replacement ratio with 0.6, 0.8 and 1.0 penetration ratio has a shear strength increment of 25.22%, 33.39% and 37.59% respectively. In short, the shear strength improvement of the kaolin clay depends on the parameter of the PP column used to reinforce the sample.